Catalyst for Change : Empowering Women and Tackling Income Inequality - Gonzales, Christian; Jain-Chandra, Sonali; Kochhar, Kalpana; Newiak, Monique (Washington, D.C. : International Monetary Fund, 2015)
This study shows empirically that gender inequality and income inequality are strongly interlinked, even after controlling for standard drivers of income inequality. The study analyzes gender inequality by using and extending the United Nation's Gender Inequality Index (GII) to cover two decades for almost 140 countries,. The main finding is that an increase in the GII from perfect gender equality to perfect inequality is associated with an almost 10 points higher net Gini coefficient. For advanced countries, with higher gender equity in opportunities, income inequality arises mainly through gender gaps in economic participation. For emerging market and developing countries, inequality of opportunity, in particular in education and health, appear to pose larger obstacles to income equality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet